Dangerous Earth an introduction to geologic hazards - Murck, Barbara Winifred 1954- (John Wiley & Sons, 1997)
This book contains complete coverage of the geologic processes behind major natural hazards -- earthquakes, volcanoes, landslides, floods, hurricanes. It also provides an absorbing exploration of the human-planet relationship, describing how Earth processes influence our lives on a daily basis and how human actions alter the natural functioning of Earth systems. It explains how to distinguish the effects of anthropogenic change from natural change and predict the impact of both.